Toxicological analysis Hits By Monitoring Air Quality - Inche Mitma, Jorge Luis (2000)
This study deals with the fuel emissions and their impact on the environment. It aims to identify and assess air pollutants at various points in the city of Lima, to establish preventive measures to reduce pollutants. This study finds an increase of 50% specifically in phase sampling and measurement.